Two algorithms for decomposition of a numerical semigroup as an intersection of irreducibles - Branco, M.B. (2012)
Every numerical semigroup S admits a decomposition S = S1 \· · ·\Sn with Si irreducible (that is, Si is symmetric or pseudo-symmetric) for all i. We compare two different algorithms to obtain a numerical semigroup as intersection of irreducibles numerical semigroups.